PEMANFAATAN AI (ARTIFICIAL INTELLIGENCE) DALAM PEMBUATAN WEBSITE SEBAGAI INOVASI PENGEMBANGAN BISNIS KULINER SNACK PHOPHO - Ajisoko Tyang Pinandhito; Alfan Naufal Rabbany (STMIK Widuri Jakarta, 2025)
This study aims to provide understanding and recommendations regarding the use of Artificial Intelligence (AI) in product marketing through a website platform. The object of the research is UMKM Snack Phopho, a small business specializing in snack products, established in 2022. The method used is the implementation of AI via the durable.co platform to build a sales website that supports transactions and enhances accessibility for consumers. The results show a 35% increase in sales within 14 days and a high level of user satisfaction, as indicated by questionnaire data showing that over 85% of respondents provided positive feedback.